Genetic homogeneity in the commercial pink shrimp Farfantepenaeus paulensis revealed by COI barcoding gene - Teodoro, S. S A [UNESP]; Terossi, M.; Costa, R. C. [UNESP]; Mantelatto, F. L. (Elsevier, 2015)
The pink shrimp Farfantepenaeus paulensis is one of the most commercially exploited species in Brazil's South and Southeastern regions. Specific information about the status of its genetic variation is necessary to promote more effective management procedures. The genetic variation of the population of F. paulensis was investigated in five localities along southern and southeastern coast of Brazil. Sampling was performed with a commercial fishing boat. Total genomic DNA was extracted from abdominal muscle tissues and was used to DNA amplification by PCR. The COI gene was used as a DNA barcoding marker. The 570 bp COI gene sequences were obtained from all 45 individuals. The haplotype network showed no genetic variability among the population stocks, which was confirmed by Molecular Variance Analysis. The final alignment showed that inside species there is haplotype sharing among the sampled localities, since one haplotype is shared by 38 individuals belonging to all the five sampled regions, with no biogeographic pattern. This result is reasonable since there are no geographical barriers or habitat disjunction that might serve as a barrier to gene flow among the sampled localities. Possible reasons and consequences of the genetic homogeneity found are discussed. The results complement ecological studies concerning the offseason: since it is a single stock, the same protection strategy can be applied. However, the genetic homogeneity found in this study combined with the intensive fishery effort and the species biology can result in severe consequences for the F. paulensis.
Keywords: Cytochrome oxidase I; Fishery stocks; Gene flow; Genetic homogeneity; Penaeidae